Management of Invasive Alien Plant species through their Traditional ethno Medicinal and Socio-economic uses in the Shivalik Hills of Himachal Pradesh, India - Dogra, Kuldip S; Sharma, Renu; Ambrish, Kumar; Singh, Ritesh Kumar; Youdhveer (Indian Forester, 2024)
The scientists have tried many biological and mechanical methods for the management and control of invasive plant species from the invaded habitats but succeeded only partially as these methods are not cost effective. Thus, in the present study a new approach has been adopted for their management through the traditional ethno-medicinal and socio-economic uses of invasive alien plant species occurring in the Shivalik hills of Himachal Pradesh. A total of 85 most dominant invasive alien plant species, were selected and information was collected regarding their traditional ethnomedicinal and socio-economic uses from the local rural peoples of the villages using a semi-structured questionnaire. Habit wise analysis of IAPS shows 62% species are herbs, 16% shrubs, 8% grasses, 7% trees, 4% under shrub, and 1.5% are represented by climbers and aquatic plant species each. Of the total Invasive alien plant species observed, 72% (62 plant species) were used for Ethno-medicinal purposes and 28% (24 plant species) of the plant species are used for socio-economic purposes. Most of the plants are traditionally used for the treatment of 36 different types of ailmemts as ethnomedicines and for 6 different types of socio-economic purposes such as food, fodder, fuel wood, religious prayers and for making baskets. Out of 85 species, 25 species are invasive, 20 species are naturalized, 1 species (Populus alba L.) is cultivated, and 39 species are casual invaders in the study area. The per cent use values indicate that about 55% of the total plant species have more than 50% use value and only 4% showed the value above 90% which clearly indicates the frequent use of these species by rural communities in the Shivalik hills. Thus, the information generated from this study to document the ethno-medicinal and socio-economic uses of the IAPS for the management and control by using their extra load of biomass from the invaded habitats in study area.